2016
DOI: 10.1038/srep27152
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induced CCL28 promotes angiogenesis in lung adenocarcinoma by targeting CCR3 on endothelial cells

Abstract: Tumor hypoxia is one of the important features of lung adenocarcinoma. Chemokines might mediate the effects caused by tumor hypoxia. As confirmed in tumor tissue and serum of patients, CC chemokine 28 (CCL28) was the only hypoxia induced chemokine in lung adenocarcinoma cells. CCL28 could promote tube formation, migration and proliferation of endothelial cells. In addition, angiogenesis was promoted by CCL28 in the chick chorioallantoic membrane and matrigel implanted in dorsal back of athymic nude mice (CByJ.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 38 publications
0
70
0
Order By: Relevance
“…However, numerous in vitro studies show that CCL28 and CCL27 support tumor development ( Figure 7 ). For this reason, some researchers suggest that CCL28 can act locally, especially in the hypoxic regions of the tumor [ 14 , 16 , 17 , 321 , 322 ]. CCL28 and CCL27 stimulate proliferation and have anti-apoptotic effects on cancer cells [ 323 , 324 , 325 ].…”
Section: Ccr10 Ccl28 and Ccl27mentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous in vitro studies show that CCL28 and CCL27 support tumor development ( Figure 7 ). For this reason, some researchers suggest that CCL28 can act locally, especially in the hypoxic regions of the tumor [ 14 , 16 , 17 , 321 , 322 ]. CCL28 and CCL27 stimulate proliferation and have anti-apoptotic effects on cancer cells [ 323 , 324 , 325 ].…”
Section: Ccr10 Ccl28 and Ccl27mentioning
confidence: 99%
“…The CCL27→CCR10 axis has also been shown to be involved in the recruitment of Th22 to malignant ascites; even though no effect of an increased number of these cells on patient prognosis has been demonstrated [ 331 ], Th22 may have a pro-cancer effect, as shown in a study on colorectal cancer [ 332 ]. In turn, CCL28 causes angiogenesis by activating CCR3 on vascular endothelial cells [ 322 ]. Both chemokines, CCL28 and CCL27, cause lymphangiogenesis by activating CCR10 on lymphatic endothelial cells [ 333 ].…”
Section: Ccr10 Ccl28 and Ccl27mentioning
confidence: 99%
“…The induction of CCL28 in tumor cells was suggested to enhance cytotoxicity by attracting CCR10-expressing activated NK cells toward tumor sites (51). On the other hand, upregulated CCL28 under hypoxic conditions has been shown to promote angiogenesis via endothelial CCR3 in lung adenocarcinoma and recruitment of Tregs and tumor growth in liver and ovarian cancer (52)(53)(54). CCL28 overexpression stimulated breast cancer growth and metastasis by upregulating the antiapoptotic protein Bcl-2 and suppressing β-catenin (55) and promoted esophageal SCC cell migration (56).…”
Section: Ccl28 Treatment Inhibits Invasion and Emt In Oscc Cellsmentioning
confidence: 99%
“…That study pointed that in adenocarcinoma, CCL28 could be induced by hypoxia and acted as a chemokine to promote angiogenesis through targeting C-C motif chemokine receptor (CCR)3 on microvascular endothelial cells. [ 38 ] Recent report revealed that CCR7,might indicate lymph node metastasis of various cancers including lung cancer. The CCL21/CCR7chemotaxis could interact with EMT procedures and finally promoted lung cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%